2018
DOI: 10.1021/acsami.8b05034
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of Versatile Surface Morphologies on Hot Dip Galvanized Steel in Wet CO2: Aspects on Formation, Barrier Properties, and Utilization as a Substrate for Coatings

Abstract: Zinc carbonate and a mixed-phase zinc carbonate were precipitated selectively on hot dip galvanized steel in the presence of CO and water. The zinc carbonate was precipitated as a uniform layer with cubic superficial appearance, while the mixed-phase zinc carbonate was precipitated as nanowires. The distinct structures could be formed separately or as a dual structure with nanowires on the outermost surface. The barrier properties were improved by the both patina forms; a significant increase in surface hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…[37,[40][41][42] A more detailed breakdown of the specific vibrations can be found in the literature. [43] These observations are consistent with earlier findings with early corrosion products being zinc hydroxycarbonate and the latter corrosion products (anhydrous) zinc carbonate. [44,45]…”
Section: Corrosion Product Characterizationsupporting
confidence: 92%
“…[37,[40][41][42] A more detailed breakdown of the specific vibrations can be found in the literature. [43] These observations are consistent with earlier findings with early corrosion products being zinc hydroxycarbonate and the latter corrosion products (anhydrous) zinc carbonate. [44,45]…”
Section: Corrosion Product Characterizationsupporting
confidence: 92%
“…The interpretations of the spectra were based on the reference spectra of zinc compounds presented in previous publications. [ 16,20 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 15,17 ] Zinc patina layers possess high hydrophobicity, which could lead to an efficient barrier against metal corrosion. [ 20,22 ] In salt‐containing environments, complex zinc corrosion products (not Zn(OH) 2 or ZnO), possessing a negatively charged surface, have further been shown to aid in the repulsion of chloride ions [ 18 ] and increase the barrier effect against oxygen diffusion. [ 24 ] In other studies, this same phenomenon was confirmed by a decrease in oxygen reduction on the surface, measured as a decreased cathodic current, providing clear experimental evidence of the barrier effect.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of the P.Patina surfaces (P.Patina‐1 and P.Patina‐2) are described elsewhere. [ 18 ] A hot dipped galvanized surface was exposed in parallel and used as reference (Zn‐sheet), and to investigate how a fresh nonexposed Zn surface (with a thin surface oxide) differs from a naturally aged surface (N.Patina at repeated dry and wet conditions, e.g., during outdoor storage). The aged reference surfaces (N.Patina) were prepared by exposing fresh Zn‐sheet surfaces to repeated dry/wet cyclic exposures (3 h at 40°C/90% RH, 3 h at 10°C/90% RH, 3 h at 40°C/20% RH, and 3 h at 10°C/20% RH) in a Weiss WK3 340/40 climate chamber for 3 weeks.…”
Section: Methodsmentioning
confidence: 99%